The social and psychological context of the concept of management (Economics and region, 2025)
The article considers the modern concept of management as a complex socio-psychological system that goes beyond purely technical and organizational aspects. The authors analyze the relationship between management activities, interpersonal relationships in the organization, group dynamics, and key motivational factors. Particular attention is paid to highlighting the social influence of the manager, his leadership qualities, the role of corporate culture and effective communications in creating a favorable and productive management environment, and ensuring adequate personnel security. The study focuses on revealing the peculiarities of interaction between managers and subordinates, the mechanisms of forming group norms, team cohesion, and the influence of organizational culture on employee behavior. Concepts explaining the psychological nature of motivation and its impact on improving work efficiency are considered. The critical need to integrate deep psychological knowledge into modern management practice for an adequate understanding of human behavior in an organization is justified. The importance of emotional intelligence as a key competence of a manager, which allows them to effectively manage their own emotions and understand the feelings of subordinates, is investigated. It is emphasized that leadership in the context of social psychology is not only about authority, but also about the art of inspiring and mobilizing people. This approach focuses not only on formal authority, but also on interpersonal interaction and the psychological mechanisms underlying influence. It is argued that in the context of social psychology, leadership is not so much a set of functions as a social process of influence, which is determined by the psychological characteristics of the leader and followers, group dynamics, and situational factors. Specific approaches and recommendations are proposed for improving management practices, taking into account psychological factors, which will contribute to increasing the innovation, flexibility, and overall competitiveness of the organization in the context of dynamic market changes.
Keywords: management; social psychology; emotional intelligence; organizational culture; leadership; effective communication; social capital; trust; positive microclimate; personnel security